Inovasi Pembelajaran Pecahan Berbasis Metakognisi Untuk Meningkatkan Berpikir Kritis di Sekolah Dasar - Wicaksono, Samsiar Tri Bagus; Indra Dewi, Radeni Sukma; Ekawati, Ratna; Nugraha, Jaka (JURNAL PENA EDUKASI, 2025)
The critical thinking skills of elementary school students in mathematics learning, espe-cially fraction materials, are still a significant challenge. This study aims to identify and explore the application of metacognition-based learning that can improve students' criti-cal thinking skills. Using the Systematic Literature Review (SLR) method of 15 scientific articles, this research examines innovative learning models that integrate metacognition in fraction learning. The research findings show that the implementation of metacognition-based learning significantly improves students' critical thinking skills in several analyzed studies. Problem-Based Learning (PBL), Numbered Head Together (NHT), and STEM-PJBL approaches proved effective in facilitating the development of critical thinking skills. In addition, the use of technology-based interactive media, such as the “Merica” application, also contributed positively to students' understanding of the concept of fractions. The implication of this research is the need for curriculum develop-ment that is more integrated with metacognitive strategies, especially in mathematics learning at the elementary school level. This implication provides practical guidance for teachers and curriculum developers in designing more effective and targeted metacognition based learning. Thus, this research is expected to encourage the development of mathematics learning innovations that are more effective and student centered